2019
DOI: 10.1159/000496164
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Ameliorates Angiotensin II-Induced Human Endothelial Progenitor Cell Injury via the PPAR-γ/HO-1 Pathway

Abstract: Vitamin D has an important protective effect on chronic inflammatory disease. Angiotensin II (AngII) triggers vascular damage and plays a key role in vascular diseases via several mechanisms, including inflammation. Conversely, vitamin D has been shown to have an important protective effect on chronic inflammation. There is evidence showing that vitamin D can reverse the effects of AngII, but the molecular mechanisms by which this occurs are not known. Our results demonstrate that vitamin D improved the viabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 37 publications
(34 reference statements)
1
7
0
Order By: Relevance
“…HO-1 deletion in myeloid cells promotes the polarization of proinflammatory M1 macrophages both in vivo and ex vivo, while transgenic overexpression of HO-1 favors an M2 anti-inflammatory phenotype [57], revealing a regulatory role of HO-1 in macrophage inflammation and atherogenesis. Additionally, activation of PPARγ has been shown to reduce proinflammatory cytokine secretion by upregulating HO-1 expression in multiple cell types [58,59]. The present study demonstrated that knockdown of PPARγ, LXRα, and HO-1 with siRNAs abolished the inhibitory effect of BCA on TNF-α, IL-1β, and IL-6 secretion from THP-1 macrophage-derived foam cells.…”
Section: Discussionsupporting
confidence: 56%
“…HO-1 deletion in myeloid cells promotes the polarization of proinflammatory M1 macrophages both in vivo and ex vivo, while transgenic overexpression of HO-1 favors an M2 anti-inflammatory phenotype [57], revealing a regulatory role of HO-1 in macrophage inflammation and atherogenesis. Additionally, activation of PPARγ has been shown to reduce proinflammatory cytokine secretion by upregulating HO-1 expression in multiple cell types [58,59]. The present study demonstrated that knockdown of PPARγ, LXRα, and HO-1 with siRNAs abolished the inhibitory effect of BCA on TNF-α, IL-1β, and IL-6 secretion from THP-1 macrophage-derived foam cells.…”
Section: Discussionsupporting
confidence: 56%
“…Wei Xu et al studied the effect of vitamin D on endothelial progenitor cells (EPCs) pretreated with AngII. Their study demonstrated that vitamin D reversed AngII-induced oxidative stress injury by the peroxisome proliferator-activated receptor-γ (PPAR-γ) pathway [108]. PPAR-γ lowers the production of superoxide and enhances the repair capacity of EPCs [109].…”
Section: Role Of Vitamin D In the Endothelial Cell Activationmentioning
confidence: 99%
“…[1] The partial agonist of PPAR-γ has been extensively studied in some angiotensin type 1 receptor (ATR1) blockers. [3][4][5] Studies have shown that Telmisartan induces PPAR-γ activity despite ATR1 being absent, making it more evident that its stimulation occurs despite ATR1 blockade. Studies are showing the evidence of the relationship between some angiotensin receptor blockers (ARBs) with PPAR-γ by their binding to the PPAR-γ receptor.…”
Section: Introductionmentioning
confidence: 99%